The Dynamics Of Islamic Education Policy In Indonesia: Historical Traces Across Eras (Pre-Independence - Reform) - Padlianor; Lyindira Putri; Siti Aisyah; Dina Hermina (PT. Hasba Edukasi Mandiri, 2025)
This study examines the long and diverse history of Islamic education policies in Indonesia, from the pre-independence era to the present day. The study aims to trace the evolution of these policies, analyse the various policies issued by the government, and assess their impact on the advancement of Islamic education in Indonesia. This research employs a qualitative literature review approach, examining various sources such as books, journals, and relevant documents. The findings reveal significant changes in Islamic education policies over time. During the Dutch colonial period, policies tended to restrict its development. After independence, the Indonesian government gave greater attention to Islamic education, although challenges persisted. The Reform Era brought important changes by granting greater autonomy to Islamic educational institutions. In conclusion, Islamic education policies in Indonesia continue to evolve and are influenced by social, political, and cultural factors. This study is expected to provide a deeper understanding of the evolution of these policies and the challenges and opportunities in the development of Islamic education in the future